2002
DOI: 10.1002/jsfa.1119
|View full text |Cite
|
Sign up to set email alerts
|

Browning in processed yams: peroxidase or polyphenol oxidase?

Abstract: Polyphenol oxidase and peroxidase were puri®ed from white yam (Dioscorea rotundata) using DEAE-cellulose ionexchange chromatography. Thermoinactivation curves for polyphenol oxidase showed monophasic kinetics, while those for peroxidase were biphasic. Urea partially stabilised peroxidase against irreversible thermoinactivation, but did not do so in the case of polyphenol oxidase. Only peroxidase was capable of regenerating activity after thermoinactivation. The results showed that thermoinactivation of peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
0
17
1
2
Order By: Relevance
“…Drying can improve shelf life of watery tubers and a unique process has been developed for yam in Nigeria and Benin that includes hand peeling, blanching in water at 63 ± 3 • C, and sun drying for 5-7 days [3]. Tubers from Dioscorea rotundata cultivars, and particularly from the kokoro group, are generally used for this process [4]. They are thought to give the best amala, the paste obtained from dry yam flour.…”
Section: Introductionmentioning
confidence: 99%
“…Drying can improve shelf life of watery tubers and a unique process has been developed for yam in Nigeria and Benin that includes hand peeling, blanching in water at 63 ± 3 • C, and sun drying for 5-7 days [3]. Tubers from Dioscorea rotundata cultivars, and particularly from the kokoro group, are generally used for this process [4]. They are thought to give the best amala, the paste obtained from dry yam flour.…”
Section: Introductionmentioning
confidence: 99%
“…), which remove copper from the active site of the enzyme 26 . Chilaka et al reported that thiourea was a good inhibitor of PPO, with low Ki values of 0.15 mM and inhibition of PPO was uncompetitive 27 . We were determined that (3), (4), (5a), (5c), (5d), (5e), (5f), and (5g) was a better inhibitor of PPO according to thiourea.…”
Section: Resultsmentioning
confidence: 99%
“…On heating HR-POD at 70°C in acetate buffer at pH 5.6, strong activity regeneration is observed after short heating time whilst weak regeneration is observed after long heating time. The major reason for this behavior is the existence of isoenzymes with different heat-stability in vegetables (Chilaka et al, 2002). Ramesh et al (2002) reported the results of using pulsed microwave to blanch spinach, carrot, and bell peppers at 95°C, and established the kinetics of POD inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…This is a unique phenomenon of regeneration of POD and an important characteristic of POD. Chilaka et al (2002) reported that regeneration of POD activity after thermal inactivation is common in plants and attributed this to quality deterioration of partially blanched vegetables during storage. Reports on regeneration of polyphenoloxidases are rare (Ke, 1998).…”
Section: Introductionmentioning
confidence: 99%